Pendidikan Islam di Mesir, India, dan Pakistan - Yesi Arikarani (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2019)
Islamic education enters along with the early history of Islam in the form of civilization such as the Egyptian culture of the pyramids, sphinxes, obelisks, and hieroglyphics. the figures who have contributed to the field of education are Muhammad Abduh, Sayyid Ahmad Khan, and Muhammad Ali Jinnah. The application of education between Egypt, India, and Pakistan is almost the same, namely making compulsory education for their citizens. The existence of public and religious/Madrasah educational institutions as well as public and religious high schools / universities. Different curriculum. Application of the learning of the Qur'an and Hadith. Integrate between general science and religious science. professional teaching staff. Every country has a different education system influenced by sociology of society, the history of the establishment of a country, the needs of a country in accordance with the demands of the era and an increasingly globalized world.